Pengaruh Nilai Tukar, Jumlah Uang Beredar, dan IHSG terhadap Nilai Aktiva Bersih Reksadana Syariah Tahun 2019-2021 - Zein Wiratama Yudhanto; Citra Mulya Sari (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This study aims to determine the extent of the influence of the exchange rate, the money supply and the JCI on the Net Asset Value of Islamic Mutual Funds in 2019-2021. This research uses quantitative research and Time Series analysis through SPSS. As a data analysis technique. The results of this study indicate that the Exchange Rate, the Money Supply and the JCI have a significant simultaneous effect on the Net Asset Value of Islamic Mutual Funds 2019-2021. Based on the t test, it shows that the Exchange Rate (X1) has no significant effect on the Net Asset Value of Islamic Mutual Funds 2019-2021. The Money Supply (X2) has no significant effect on the Net Asset Value of Islamic Mutual Funds 2019-2021. JCI (X3) has a significant effect on the Net Asset Value of Islamic Mutual Funds 2019-2021. Keywords: Exchange Rate, Money Supply, JCI, Net Asset Value, Sharia Mutual Funds